Características físico-químicas, cozimento e produtividade de mandioca cultivar IAC 576-70 em diferentes épocas de colheita. - de Oliveira, Marcelo Alvares (2009)
The instability of cassava culinary quality is a problem in the market. This work had the purpose of evaluating the interference of the productivity, rain precipitation and physical-chemical characteristics on the cooking time of the IAC 576-70 cultivar, from the 6(th) to the 12(th) month after the planting. The physical parameters evaluated were: difficulty in peeling (easy, medium, and hard), difficulty in cutting in long, thin sticks with a manual machine, being those cut in a subjective way. In the analysis of the cooked root, the percentage of water absorbed into the cassava pieces, the color, white points formed inside the pieces of cassava, gel formation around the pieces of cassava, and cooking time were evaluated. The pH, acidity, moisture, ashes, fibers, ether extract, protein, reducing sugars, and starch of the roots were also monthly evaluated. From the results obtained in the present work, it may be concluded that the cassava IAC 576-70, when planted in July, in Botucatu-SP area, must be harvested at the age of nine months, without damage to the productivity, starch level and root cooking, and the harvest could be extended up to ten months. The producers should follow the sum of precipitation index ten days before the harvest, and this value should be the smallest as it may be and the producers should not harvest when this value is more than 100 mm, in order not to hinder the cooking of the root.